Philosophy and theology in the Middle Ages - Evans, G. R. (Gillian Rosemary) (Routledge, 1993)
In the ancient world being a philosopher was a practical alternative to being a christian. Philosophical systems offered intellectual, practical and moral codes for living. By the Middle Ages however philosophy was largely, though inconsistently, incorporated into Christian belef. From the end of the Roman Empire to the Reformation and Renaissance of the sixteenth century Christian theologians had a virtual monopoly on higher education. The complex interaction between theology and philosophy, which was the result of the efforts of Christian leaders and thinkers to assimilate the most sophi.